The souls of Lost Lake [large type] - Wright, Jaime Jo (Thorndike large print Christian fiction series., 2022)
"To save the innocent, they must face an insidious evil. Wren Blythe has long enjoyed living in the Northwoods of Wisconsin, helping her father with ministry at a youth camp. But when a little girl in the area goes missing, an all-out search ensues, reviving the decades-old campfire story of Ava Coons, the murderess who is believed to still roam the forest. Joining the search, Wren stumbles upon the Coonses' cabin ruins and a sinister mystery she is determined to unearth.In 1930, Ava Coons has spent the last several years carrying the mantle of mystery since the day she emerged from the woods as a thirteen-year-old girl, spattered with blood, dragging a logger's ax. She has accepted she will never remember what happened to her family, whose bodies were never found, and that the people of Tempter's Creek will always blame her for their violent deaths. And after a member of the town is murdered, and another goes missing, rumors spread that Ava's secret is perhaps more malicious than previously imagined.Two women, separated by time, must confront a wickedness that not only challenges who they are but also threatens their lives, and the lives of those they love"--